THE NEW STATE'S MOVIE THEATER IN THE BRAZILIAN MIDWEST - Calori de Lion, Antonio Ricardo [UNESP] (Pontificia Univ Catolica Sao Paulo, 2017)
This article seeks to discuss the process of urban intervention in the capitals of the Brazilian Midwest, looking at the constructions of the movie theater built in the management of the Interventors Pedro Ludovico Teixeira and Julio S. Muller, in the first half of the 1940s. Starting from the bibliographical discussion on the March to the West, in the passage from the 1930s to the 40s, the buildings destined for culture are chosen as objects of reflection in the meanings of their symbolizations given by the agents of that political moment.
Keywords: Cine-Teatro Cuiaba; Cine-Teatro Goiania; Modernization; Brazilian New State